Public Policy-Based Disaster Mitigation Strategy In Sembalun - Taufiqurohman, Taufiqurohman; Suryanto, Totok; Adnyana, I Made Susila; Shoum A, Sholahuddin (Indonesian Journal of Social Science Research, 2025)
Sembalun is a disaster-prone region facing threats such as earthquakes, landslides, and extreme weather. This study aims to analyze non-structural disaster mitigation strategies implemented through public policy in Sembalun. The research employs a qualitative approach through literature review and case studies. The findings reveal that non-structural mitigation policies still face challenges in regulatory implementation, community participation, and institutional capacity. However, there is significant potential in integrating local wisdom, such as the nengah bulan system, and using culturally-based disaster education. Community agroforestry initiatives in buffer zones highlight the crucial role of grassroots efforts in disaster risk reduction. This study recommends the need for adaptive policies that bridge modern technology with indigenous knowledge and promote a paradigm shift toward community-based planning